Increased rate of any retinopathy risk in patients with masked hypertension. (17th August 2020) - Yıldırım, Timuçin; Özkan, Selçuk; Yılmaz, Ömer Çağlar; Yavuz, Bunyamin
ABSTRACT: Purpose: Hypertension is a common chronic disorder with end organ damage. Hypertensive retinopathy is a response to elevated blood pressure characterized retinal arteriolar intimal thickening, hyperplasia of the intima-media end with sclerosis. There is a relationship between high blood pressure and retinopathy grade. Masked hypertension is a phenomenon of normal blood pressure in the office but high in out of office that associated with an increases risk of cardiovascular disease. In this study, we aimed to investigate retinopathy in masked hypertensive patients. Methods: We enrolled 92 patients with masked hypertension and 87 healthy controls in to the study. We use ambulatory blood pressure monitoring (ABPM) to detect the masked hypertension. Bilateral fundus examination was performed. Hypertensive retinopathy (HTRP) grading was determined according to the Keith–Wagener–Barker classification. We examined retinopathy grade in patients with masked hypertension and without. Results: 55 (11.6%) participants had signs of retinopathy. Fifty (54.3%) subjects had any retinopathy in patients with masked hypertension and five (5.7%) subjects had any retinopathy in controls ( p < .001). Median of KWB grade was 1 (0–4) in patients with masked hypertension and 0 (0–2) in controls ( p < .001). There were a positive significant correlation between KWB grade and day-time systolic blood pressure (r = 0.460, p < .001), day-time diastolic blood pressure (r = 0.448, p < .001), presence of masked hypertension (r = 0.527, p < .001). Conclusions: There was a considerable rate of any retinopathy in masked hypertension. Consequently, ophthalmoscopic examination should be as part of the care in patients who have a risk for masked hypertension.